2014
DOI: 10.1111/all.12495
|View full text |Cite
|
Sign up to set email alerts
|

Replication of genomewide associations with allergic sensitization and allergic rhinitis

Abstract: The TLR6-TLR1 locus is likely to have a central role in the development of allergic disease. The association between genetic variation in the SSTR1-MIPOL1 and TSLP-SLC25A46 loci and age at onset is the first report of age at onset effects in allergic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…The TLR6 is located on chromosome 4p14, a region that was consistently associated with atopy in three GWAS161718. Early-onset asthma is more likely to be attributable to atopy15 and therefore it is not surprising to observe some evidence for the association between the two TLR6 SNPs and early-onset asthma but not late-onset asthma in our study.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The TLR6 is located on chromosome 4p14, a region that was consistently associated with atopy in three GWAS161718. Early-onset asthma is more likely to be attributable to atopy15 and therefore it is not surprising to observe some evidence for the association between the two TLR6 SNPs and early-onset asthma but not late-onset asthma in our study.…”
Section: Discussionmentioning
confidence: 47%
“…The selection of CD14 rs2569190, rs5744455 and rs2915863 SNPs were based on their relationship with asthma or wheeze, sensitisation or hay fever12. The TLR6 rs5743810 and rs1039559 SNPs was selected because they have been shown to be associated with hay fever and sensitisation in three large GWAS studies161718. The SNPs from the TLR2 and TLR4 were selected based on the associations shown with asthma and atopy, and their effect modification by farming exposure in a previous study19.…”
mentioning
confidence: 99%
“…TSLP polymorphisms have been studied in the context of respiratory [12,13,14,35,36,37] and cutaneous diseases [10,11], including NERD [9]. However, in this study only two imputed SNPs showed a nominal genetic association (rs1816678 and rs764917) with NIUA, suggesting a potential role of TSLP in NIUA, although this must be confirmed.…”
Section: Discussionmentioning
confidence: 63%
“…Several candidate gene association studies have assessed the importance of TSLP in NSAID-exacerbated respiratory disease (NERD) [9], atopic dermatitis [10] and eczema [11], as well as other allergy-related pathologies. In addition, genome-wide association studies have found single nucleotide polymorphism (SNPs) in TSLP to be associated with asthma [12], allergic rhinitis [13,14] and eosinophilic esophagitis in children [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Similarly to IL-33, SNPs in the TSLP gene region have been associated with asthma as broad diagnosis (Hunninghake et al, 2010;Torgerson et al, 2011), but also with allergic rhinitis (Nilsson et al, 2014;Ramasamy et al, 2011), and recently with the combined asthma and hay fever phenotype (Ferreira et al, 2014), suggesting a potential role of TSLP in allergic phenotypes. SNPs in the latter gene region are both located upstream and intragenic, still allowing several functional roles in TSLP biology, including an eQTL function and a role in protein binding (Ober and Yao, 2011;Papazian et al, 2014).…”
Section: Genetic and Clinical Evidence For The Role Of Il-33 And Tslpmentioning
confidence: 99%